Atomic Layer Deposition of Metal Oxide on Nanocellulose for Enabling Microscopic Characterization of Polymer Nanocomposites. Issue 46 (16th October 2018) - Septevani, Athanasia A.; Evans, David A. C.; Hosseinmardi, Alireza; Martin, Darren J.; Simonsen, John; Conley, John F.; Annamalai, Pratheep K.
Abstract: Analysis of cellulose nanocrystals (CNCs) at low volume fractions in polymer nanocomposites through conventional electron microscopy still remains a challenge due to insufficient contrast between CNCs and organic polymer matrices. Herein, a methodology for enhancing the contrast of CNC, through atomic layer deposition (ALD) of alumina (Al2 O3 ) on CNCs is demonstrated. The metal oxide coated CNC allows clear visualization by transmission electron microscopy, when they are dispersed in water and polyol. A coating of about 6 ± 1 nm thick alumina layer on the CNC is achieved after 50 ALD cycles. This also enables the characterization of CNC dispersion/orientation (at 0.2 wt% loading) in an amorphous cellular system rigid polyurethane foam (RPUF), using backscattered electron microscopy with energy‐dispersive X‐ray spectroscopy. Microscopic analysis of the RPUF with alumina‐coated CNC confirms that the predominant alignment of CNC occurs in a direction parallel to the foam rise. Abstract : Characterization of organic nanoparticle orientation in polyurethane (PU) foam, which exhibits anisotropic mechanical properties, remains challenging. This Communication briefly demonstrates the application of atomic layer deposition for enhancing the contrast of nanocellulose (nanocrystal, CNC) through a thin layer coating of alumina and enabling microscopic characterization. By incorporating alumina‐coated nanocellulose in a PU foam, it also demonstrates nanocellulose alignment in the foam‐rise direction.